Application of Various Dosages of Solid Organic Fertilizer Derived from Corn Waste on The Growth and Yield of Water Spinach (Ipomoea reptans Poir.): Aplikasi Berbagai Dosis Pupuk Organik Padat Limbah Jagung terhadap Pertumbuhan dan Produksi Tanaman Kangkung Darat (Ipomoea reptans Poir.) - Rival Rahman; Silviana Arsyad; Echan Adam; Nurdin; Hidayat Arismunandar Katili; Eka Saputra Samadi; Rahmad Napidu; Lihan Laraga; Mohammad Rian; Sri Alda S. Sapiullah; Hasni Husain (Faculty of Agriculture, Tompotika Luwuk University, 2026)
The use of solid organic fertilizer from corn waste is an alternative to support sustainable agricultural systems and reduce dependence on inorganic fertilizers. This study aims to determine the application of various doses of solid organic fertilizer from corn waste on the growth and production of land spinach plants and to determine the fertilizer dose that provides the best response. The study was conducted using a Randomized Block Design with five solid organic fertilizer doses: 0, 4, 6, 8, and 10 kg per plot. Observed parameters included plant height, number of leaves, and plant fresh weight. Data were analyzed using analysis of variance and continued with a LSD test at the 5% level if there were significant differences between treatments. The results showed that the application of solid organic fertilizer from corn waste had a significant effect on plant height at 12 and 15 days after planting and the number of leaves at 18 days after planting, but had no significant effect on plant fresh weight. A fertilizer dose of 4 kg per plot provided the best vegetative growth response compared to higher doses or no organic fertilizer.